2020
DOI: 10.21608/ejpt.2020.77844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Craniovertebral Angle and Shoulder Angle in Egyptian Adolescents

Abstract: Purpose: To explore the effect of body mass index (BMI) on Craniovertebral Angle (CVA) and Shoulder Angle (SA) in Egyptian Adolescents. Methods: Cross Sectional Study designe was used. Eighty-six physical therapy students were selected randomly, and their age were ranged from 18-27 years. They were divided into three groups according to BMI. The first group with normal BMI (18.5-24.9 Kg/m 2 ), while the second group was overweight (BMI was ranged from 25-29.9 Kg/m 2 ). The third group was obesity class I (BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Furthermore, the CVA correlates with higher cervical proprioception. 24,25 Right neck rotation was associated with CP in this study. Consistent with these results, previous studies showed that individuals suffering from chronic, nontraumatic cervical spine pain and cervical spondylosis had a range of motion of 6.3° in flexion, 5.2° in extension, 6.9° in right rotation, and 4.2° in left rotation of the JPE 10 .…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, the CVA correlates with higher cervical proprioception. 24,25 Right neck rotation was associated with CP in this study. Consistent with these results, previous studies showed that individuals suffering from chronic, nontraumatic cervical spine pain and cervical spondylosis had a range of motion of 6.3° in flexion, 5.2° in extension, 6.9° in right rotation, and 4.2° in left rotation of the JPE 10 .…”
Section: Discussionsupporting
confidence: 52%